Case reportPerforation of the left atrium and aortic bulb two years after percutaneous closure of atrial septal defect - Stankiewicz, Adrian; Matlak, Krzysztof; Juszczyk, Grzegorz; Sewastianowicz, Adam; Dobrzycki, Sławomir; Poniatowski, Bogusław; Hirnle, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Non-surgical closure of the atrial septal defect (ASD) is an effective and safe method of treatment and major complications are rare. The paper reported a case of female with ischaemic heart disease, 2 years after percutaneous closure of atrial septal defect using CARDIA Closure Device. She was admitted to the Department of Cardiac Surgery for CABG procedure. During operation we found perforation of the left atrium and aortic bulb caused by the CARDIA Closure Device’s arms. This changed the extent of the planned procedure and forced the surgeon to perform an extensive, atypical heart operation finally complicated by death. Based on presented case, we believe that indications for coronary angiography before planned percutaneous ASD should be extended. Patients with an implanted occluder who require heart surgery for any reasons should undergo a computed tomography or magnetic resonance imaging scan to assess all artificial devices and their relation to anatomical structures and heart chambers.